On exiting after voting - Berga, Dolors; Bergantiños, Gustavo; Massó, Jordi; Neme, Alejandro (Estudios de Economía, 2016)
We consider the problem of a society whose members must choose from a finite set of alternatives. After knowing the chosen alternative, members may reconsider their membership in the society by either staying or exiting. In turn, and as a consequence of the exit of some of its members, other members might now find undesirable to belong to the society as well. We analyze the voting behavior of members who take into account the effect of their votes not only on the chosen alternative, but also on the final composition of the society.